2017
DOI: 10.1007/s11418-017-1097-2
|View full text |Cite|
|
Sign up to set email alerts
|

Semisynthesis and biological evaluation of prenylated resveratrol derivatives as multi-targeted agents for Alzheimer’s disease

Abstract: A series of prenylated resveratrol derivatives were designed, semisynthesized and biologically evaluated for inhibition of β-secretase (BACE1) and amyloid-β (Aβ) aggregation as well as free radical scavenging and neuroprotective and neuritogenic activities, as potential novel multifunctional agents against Alzheimer's disease (AD). The results showed that compound 4b exhibited good anti-Aβ aggregation (IC = 4.78 µM) and antioxidant activity (IC = 41.22 µM) and moderate anti-BACE1 inhibitory activity (23.70% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Puksasook et al [25] found that 4-prenylresveratrol exhibited better anti-Aβ aggregation activity than resveratrol and similar anti-BACE inhibitory activity. Other modifications on resveratrol such as imine resveratrol derivatives, [26] resveratrol tacrine hybrids [27] and resveratrol clioquinol hybrids [28] have also been explored as neuroprotective agents.…”
Section: Fig 1 Resveratrol and Related Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Puksasook et al [25] found that 4-prenylresveratrol exhibited better anti-Aβ aggregation activity than resveratrol and similar anti-BACE inhibitory activity. Other modifications on resveratrol such as imine resveratrol derivatives, [26] resveratrol tacrine hybrids [27] and resveratrol clioquinol hybrids [28] have also been explored as neuroprotective agents.…”
Section: Fig 1 Resveratrol and Related Natural Productsmentioning
confidence: 99%
“…Methyl, ethyl, isopropyl and butyl resveratrol derivatives were synthesized by random alkylation in DMF using potassium carbonate and the corresponding 1-iodoalkane (Scheme 1) [25,37]. Subsequent chromatographic separation afforded mono-, di-and trialkyl resveratrol derivatives 11-25 although several derivatives such as pterostilbene (3) could not be isolated under the chromatographic conditions used.…”
Section: Chemistrymentioning
confidence: 99%
“…4-isopentenyl-3,5,4Ј-trihydroxystilbene) as a potential lead compound for Alzheimer's disease treatment due to its multitargeting properties. Arachidin-2 inhibited ␤-secretase and amyloid-␤ aggregation and showed antioxidant, neuroprotective, and neuritogenic properties, with no neurotoxicity (23).…”
mentioning
confidence: 99%
“…The neuroprotective effect was superior to that presented by RV and was even similar to the positive control with quercetin. The replacement of the -OH groups of RV structure is associated with promising activity presented by the compound against AD (Puksasook et al, 2017).…”
Section: Prenylated Resveratrol Derivativesmentioning
confidence: 99%